1987
DOI: 10.1017/s0022112087002027
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a vortex ring on a wall

Abstract: The flow induced by a vortex ring approaching a plane wall on a trajectory normal to the wall is investigated for an incompressible fluid which is otherwise stagnant. The detailed characteristics of the interaction of the ring with the flow near the surface have been observed experimentally for a wide variety of laminar rings, using dye in water to visualize the flow in the ring as well as near the plane surface. Numerical solutions are obtained for the trajectory of the ring as well as for the unsteady bounda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
178
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(211 citation statements)
references
References 33 publications
33
178
0
Order By: Relevance
“…Moreover, the velocity profile within this region is not known, with previous studies being exclusive to a vortex ring interacting with solid (non-porous) surfaces, with axisymmetry assumed and for values of Re notably smaller than those considered here. 29,30 Hence, an analogous standard parameterisation was not possible and an alternative estimate for σ b was required, based on the available fluid velocity data. The following approach was adopted.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the velocity profile within this region is not known, with previous studies being exclusive to a vortex ring interacting with solid (non-porous) surfaces, with axisymmetry assumed and for values of Re notably smaller than those considered here. 29,30 Hence, an analogous standard parameterisation was not possible and an alternative estimate for σ b was required, based on the available fluid velocity data. The following approach was adopted.…”
Section: Resultsmentioning
confidence: 99%
“…This vorticity separates and is ejected into the inviscid flow region above as a secondary vortex ring, which then interacts with the original ͑or primary͒ vortex ring. ͑This mechanism has been studied previously [17][18][19] for the case of a vortex ring interacting with a solid boundary.͒ The secondary ring, which is not dyed, is first seen in Fig. 2 deforming the outer streamlines of the primary ring at ͑t − t 1 ͒ / = 1.1.…”
Section: Resuspension Characteristicsmentioning
confidence: 94%
“…This is similar to the behavior observed when a vortex ring interacts with a solid boundary. 17 The sequence of white crosses included in Fig. 2͑i͒ shows the trajectory of the vortex core during the interaction.…”
Section: Resuspension Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that as a vortex approaches a wall perpendicular to its direction of motion, a region with opposite vorticity is formed between its core and the wall. See for instance Walker et al [28] and Allen and Chong [7] for experimental observations and Peace and Riley [30] for numerical calculations. In our simulations, this effect is present at the lower fixed wall for φ = 0 as can be seen from figure (16) where the vorticity field is plotted as a function of position for Re = 500, Y = 0.8.…”
Section: Case Re = 500mentioning
confidence: 99%